Tentang Kemarahan Manusia - Uskono, Yeremias (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2015)
Anger inhabits every human being. There is no peace in anger. Anger tends to violence. And every outrage has a certain reason. There is a cause and effect in every rage. Angry people have basic. Anger is surely a failure in using correctly the rational and moral agent. It is not in harmony with the ideals of human life (Stoa) about “life must be in conformity with nature”. A consistent, harmonious, virtuous, and happy life should be the full expression in the development of human life; and it will be marked by action which makes sense when judged by the standards of nature. Anger could happen due to passions which come after an experience. Other words for passion are phobos (fear), epithumia (passion) and lupe (pain or wound). Passions cannot occur unless the moral agent gives ways to the idea that a particular action is reasonable. Anger is not in harmony with nature, because it is an intellectual error in interpreting the values. This paper wants to explain what anger is and how its process goes on. The writer tries to contribute in promoting the development of people towards their perfection.